Case report: Thrombotic thrombocytopenic purpura in a pregnant woman with lupus membranous nephropathy: a diagnostic challenge - Leiva, Marina; Navarro, Gustavo; Carpio, J Daniel; Ardiles, Leopoldo (Frontiers in Nephrology, 2024)
A 27-year-old female at 20th week of pregnancy was admitted with edema, foamy urine, but normal blood pressure. Her blood count was normal, she had proteinuria of 3 g/day, creatinine 0.4 mg/dl, albumin 2.4 g/dl, and cholesterol 355 mg/dl. Antinuclear antibodies 1/160, but Anti-DNA, anticardiolipin antibodies and lupus anticoagulant were negative, with normal serum C3 and C4. A renal biopsy showed secondary membranous glomerulopathy, most likely lupus class V pure. Steroids, azathioprine, and aspirin were initiated, up to 28 weeks of pregnancy, when she developed severe hypertension, photopsia, headache, anasarca, extensive bruising of the extremities, severe anemia, thrombocytopenia, and creatinine rose to 2.09 mg/dl with preserved diuresis. A female infant, 1045 grams, was delivered by emergency caesarean section. Following the surgery, she experienced diplopia, dysarthria, bradypsychia, and sensory alterations in the lower extremities, necessitating emergency hemodialysis due to pulmonary congestion. Blood smear revealed schistocytes, LDH elevated at 1148 IU/L, while transaminases and liver function remained normal, suggesting thrombotic thrombocytopenic purpura. ADAMTS13 revealed 6% activity with the presence of inhibitor. Mycophenolate and daily plasmapheresis with fresh frozen plasma replacement yielded unsatisfactory response, unaffected by the addition of methylprednisolone pulses and rituximab. Eventually, intravenous cyclophosphamide was introduced, resulting in complete hematological remission and normalization of ADAMTS13, however dialysis-dependence persisted and four years later, right renal cancer prompted bilateral nephrectomy. After a total follow-up of six years, she remained free of neoplastic recurrence and lupus activity, receiving prednisone and hydroxychloroquine. The differential diagnosis of microangiopathic syndrome in a pregnant lupus patient is discussed.